Natural and anthropogenic factors affecting the development of two highland agricultural soils of Bukidnon, Philippines - Calalang, Guadalupe D.; Bock, Laurent; Colinet, Gilles; Hallet, Vincent; Walpole, Peter (2023)
This research was conducted in two highland areas of Bukidnon, Philippines: Miarayon, a sub-catchment of the upper Cagayan de Oro River; and Bendum, a sub-catchment of the upper Pulangui River. Due to their pyroclastic parent rock materials, soils in the upper Cagayan de Oro are classified as Andic Cambisol in open and convex positions, and Andic Umbrisol in concave and depressed positions. Soils in the upper Pulangui are classified as Pisoplinthic Acrisol, Ferralic Nitisol, and Acric Nitisol in areas with ultramafic rock parent materials, and Haplic Cambisol with pyroclastic deposits. Element contents in rocks were congruent to the total soil element content analysis results except for the total calcium which was higher in Miarayon. This is attributed to the parent rocks and soil management. Total magnesium and iron were highlighted in upper Pulangui soils because of their ultramafic rock parent materials. Soil management practices and length of cultivation were identified as anthropogenic factors affecting soil development. The constant application of organic fertilizers from chicken manure had caused the build-up of organic carbon and calcium in the topsoil of Miarayon soils. The differences in total organic carbon, total nitrogen, and potassium were highly significant, particularly in soil pH and total calcium between two sites in Miarayon. In Bendum, traces of phosphate fertilizers and lime application were evidenced by the relatively higher phosphorus and calcium content in topsoil. Tillage influenced the water conductivity in soils. Organic matter content increased the water-holding capacities of soil.
Keywords: Soil fertility; Soil quality; Soils -- Mineral content